Quantitative Proteomic and Transcriptomic Study on Autotetraploid Paulownia and Its Diploid Parent Reveal Key Metabolic Processes Associated with Paulownia Autotetraploidization - Dong, Yanpeng; Deng, Minjie; Zhao, Zhenli; Fan, Guoqiang (Frontiers in Plant Science, 2016)
Polyploidy plays a very important role in speciation and plant evolution by way of genomic merging and doubling. In the process of polyploidy, rapid genomic and transcriptomic changes have been observed and researched. However, proteomic divergence caused by the effects of polyploidization is still poorly understood. In the present study, we used iTRAQ coupled with mass spectrometry to quantitatively analyze proteomic changes in the leaves of autotetraploid Paulownia and its diploid parent. A total of 2963 proteins were identified and quantified. Among them, 463 differentially abundant proteins were detected between autotetraploid Paulownia and its diploid parent, and 198 proteins were found to be non-additively abundant in autotetraploid Paulownia, suggesting the presence of non-additive protein regulation during genomic merger and doubling. We also detected 1808 protein-encoding genes in previously published RNA sequencing data. We found that 59 of the genes that showed remarkable changes at mRNA level encoded proteins with consistant changes in their abundance levels, while a further 48 genes that showed noteworthy changes in their expression levels encoded proteins with opposite changes in their abundance levels. Proteins involved in posttranslational modification, protein turnover, and response to stimulus, were significantly enriched among the non-additive proteins, which may provide some of the driving power for variation and adaptation in autopolyploids. Quantitative real-time PCR analysis verified the expression patterns of related protein-coding genes. In addition, we found that the percentage of differentially abundant proteins that matched previously reported differentially expressed genes was relatively low.